FYP student selection and examiner allocation system improvement part 1 - Tang, Wei Cong (Nanyang Technological University, 2021)
There are some components need be improved in current FYP student selection and examiner allocation system. Required skills: - Strong knowledge in OODP, PHP, SQL, Javascript (Bootstrap, JQuery), HTML/CSS Good to have: - General knowledge in security of web development (Data sanitization, SQL injections, CSRF prevention)